Role of support on higher alcohol synthesis from syngas - Lee, Jin Hee; Reddy, K. Hariprasad; Jung, Jae Sun; Yang, Eun-Hyeok; Moon, Dong Ju (ELSEVIER SCIENCE BV, 2014)
A series of Cu-Co based catalysts were prepared with different supports by co-precipitation method and well characterized by various physico-chemical methods such as N-2 adsorption, XRD, TPR, TPD NH3, TGDTA, SEM and TEM. CO hydrogenation to higher alcohols were performed and found that zinc supported catalysts showed higher conversion (70%) and selectivity towards higher alcohols (70%). It was found that the addition of CO2 to syngas enhances the conversion and selectivity. It was considered that low coordinated oxygen atoms in case of zinc supported catalyst are responsible for the high activity compared to other catalysts. It was also found that the zinc supported Cu-Co catalyst has potential for the production of higher alcohols from syngas. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: MIXED ALCOHOLS; CATALYSTS; CONVERSION; METHANOL; PRECURSORS; OXIDATION; HYDROGEN; OXIDES; CNTS; AL